Understanding the transport and CO2 impacts of on-demand meal deliveries: A London case study. (January 2021) - Allen, Julian; Piecyk, Maja; Cherrett, Tom; Juhari, Muhammad Nabil; McLeod, Fraser; Piotrowska, Marzena; Bates, Oliver; Bektas, Tolga; Cheliotis, Kostas; Friday, Adrian; Wise, Sarah
Abstract: The rise of the on-demand economy has led to a rapid increase in the delivery of meals from restaurants and fast food outlets by delivery drivers (DDs) using bicycles, mopeds and cars, with newly-established platform providers handling order and payment processing and, in many cases, the co-ordination of these deliveries. Little is currently understood about the collective transport impacts of such activity in urban centres and to what extent this poses challenges for transport policymakers. The paper provides an international review of market growth in this sector together with insight into key topics associated with its freight delivery operations in urban areas. Using a substantial database of meal deliveries made in London by a major platform provider, this paper quantifies the operational performance of these deliveries and their transport and environmental impacts. On average, 9.6 deliveries were undertaken by a DD daily, with each taking 25 min from pickup to delivery with an average trip length, from restaurant to customer of 2.2 km (1.4 miles) a DD travelling 41.3 km (25.7 miles) in total per day, The analysis of the case study indicates the relative transport inefficiency of these on-demand meal deliveries compared to other forms of urban road freight (with a meal delivered by car being responsible for approximately 1300 times the distance travelled by an articulated HGV operation per tonne delivered). It also highlights the far greater GHG emissions and transport intensity associated with meals deliveries by cars and petrol mopeds compared to bicycles (emitting 5 and 11 times more GHGs per meal delivered than bicycles, respectively). The transport and GHG emissions intensity of these meal deliveries raises important policy issues, especially given therapid growth in the provision of, and demand for, these services internationally, Based on the review and analysis, the paper provides a discussion of the key issues that urban policymakers around the world need to take account of in relation to this fast-growing sector including vehicle fuel sources, road safety, trip generation rates and their impacts on local residents, together with recommended actions. Highlights: Operating, environmental and safety issues of meal delivery reviewed internationally. Mean one-way trip distance for meal delivery is 2 km at 5.5 km per hour in dataset analysed. Greater GHG and kerb occupancy impacts for car/moped than bicycle meal deliveries. Greater vehicle kms for meals than other freight operations per tonne delivered. Discusses planning issues that policymakers should consider in relation to meal deliveries,